2022
DOI: 10.1101/2022.03.21.485165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomics Study of Bacterial Communities from Yamuna River water of city of Taj, Agra

Abstract: Yamuna river water of Agra city is heavily contaminated with toxic pollutants including heavy metal that causes severe damage to ecological and social aspects. At present, the direct use of river water for the purpose of drinking causes severe hazards due to anthropogenic activities causing environmental pollution in rivers. In present study, Yamuna River water was collected from three different sites of Agra city. Various physico-chemical parameters were estimated by following the standard methods of APHA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The most common pollution-degrading enzymes in polluted Yamuna river areas were catalase peroxidase and 4-hydroxybenzoate 3-monooxygenase. Recently Raghav et al ( 2022 ) identified organic and inorganic pollution degrading bacterial population during all seasons in Yamuna by the functional orthologies using KO.…”
Section: Riverine Ecosystemmentioning
confidence: 99%
“…The most common pollution-degrading enzymes in polluted Yamuna river areas were catalase peroxidase and 4-hydroxybenzoate 3-monooxygenase. Recently Raghav et al ( 2022 ) identified organic and inorganic pollution degrading bacterial population during all seasons in Yamuna by the functional orthologies using KO.…”
Section: Riverine Ecosystemmentioning
confidence: 99%